The Role of Thyrotropin Receptor Activation in Adipogenesis and Modulation of Fat Phenotype - Draman, Mohd Shazli; Stechman, Michael; Scott-Coombes, David; Dayan, Colin M.; Rees, Dafydd Aled; Ludgate, Marian; Zhang, Lei (Frontiers in Endocrinology, 2017)
Evidence from clinical and experimental data suggests that thyrotropin receptor (TSHR) signalling is involved in energy expenditure through its impact on white (WAT) and brown (BAT) adipose tissues. TSHR expression increases during mesenchymal stem cell (MSC) differentiation into fat. We hypothesize that TSHR activation (TSHR*, elevated TSH, thyroid stimulating antibodies (TSAB) or activating mutation), influences MSC differentiation, which contributes to body composition changes seen in hypothyroidism or Graves’ disease (GD). The role of TSHR activation on adipogenesis was first investigated using ex vivo samples. Neck fat (all euthyroid at surgery) was obtained from GD (n=11, TSAB positive), Toxic Multinodular Goitre (TMNG, TSAB negative) (n=6) and control patients with benign euthyroid disease (n=11, TSAB negative). The effect of TSHR activation was then analysed using human primary abdominal subcutaneous preadipocytes (n=16). Cells were cultured in complete medium (CM) or adipogenic medium (ADM, containing thiazolidinedione (TZD), PPAR agonist, which is able to induce BAT formation) with or without TSHR activation (gain-of-function mutant) for 3 weeks. Adipogenesis was evaluated using oil red O (ORO), counting adipogenic foci, QPCR measurement of terminal differentiation marker (LPL). BAT (PGC-1α, UCP-1 & ZIC1), pre-BAT (PRDM16), BRITE- (CITED1) or WAT (LEPTIN) markers were analysed by semi-quantitative PCR or QPCR. In ex-vivo analysis there were no differences in the expression of UCP1, PGC1α and ZIC1. BRITE marker CITED1 levels were highest in GD followed by TMNG and control (p for trend=0.009). This was associated with higher WAT marker LEPTIN level in GD than the other 2 groups (p<0.001). In primary cell culture, TSHR activation substantially enhanced adipogenesis with 1.4±0.07 (ORO); 8.6±1.8 (foci) and 5.5±1.6 (LPL) fold increases compared with controls. Surprisingly TSHR activation in CM also significantly increased pre-BAT marker PRDM16, furthermore TZD-ADM induced adipogenesis showed substantially increased BAT markers, PGC-1α and UCP1. Our study revealed that TSHR activation plays an important role in the adipogenesis process and BRITE/pre-BAT formation, which leads to WAT or BAT phenotype. It may contribute to weight loss as heat during hyperthyroidism and later transforms into WAT post-treatment of GD when patients gain excess weight.